A density functional theory study of the simplest adsorption forms of perfluorooctanoic and perfluorooctanesulphonic acids by graphene oxide and fluorinated graphene oxide*. (18th October 2022) - Gorb, Leonid; Ilchenko, Mykola; Leszczynski, Jerzy
Abstract : A density functional theory augmented by the long-range corrected hybrid density functional ωB97XD and 6-31G(d, p) basis set has been applied to generate the simplest adsorption structure models of perfluorooctanoic and perfluorooctanesulphonic acids adsorbed from a water solution by the surfaces of graphene oxide and fluorinated graphene oxide. It has been revealed that both hydrophilic and hydrophobic sites can adsorb the anions of the investigated acids. The results of our calculations suggest preference in the adsorption ability of graphene oxide compared to its fluorinated counterpart. GRAPHICAL ABSTRACT: UF0001